2014
DOI: 10.1097/dss.0000000000000221
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Smoke in Dermatologic Surgery

Abstract: Surgical smoke contains toxic compounds and particulates. Most dermatologic surgeons do not use smoke management within their practices. Raising the awareness of the potential risks can help increase the use of smoke management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…A study found that 77 % of dermatologic surgeons did not use smoke management precautions in their office [56]. This same study analyzed the smoke generated during electrosurgery and found concerning levels of toxic chemicals, including the carcinogens butadiene and benzene [56]. However, this study did not address air exchange in the operating room, which can clear the plume effectively.…”
Section: Electrosurgerymentioning
confidence: 93%
See 1 more Smart Citation
“…A study found that 77 % of dermatologic surgeons did not use smoke management precautions in their office [56]. This same study analyzed the smoke generated during electrosurgery and found concerning levels of toxic chemicals, including the carcinogens butadiene and benzene [56]. However, this study did not address air exchange in the operating room, which can clear the plume effectively.…”
Section: Electrosurgerymentioning
confidence: 93%
“…Guidelines for respiratory protection during electrosurgery are provided by the Occupational Health and Safety Agency and National Institute for Occupational Safety and Health (NIOSH) but these are not regulated and use is institution dependent [56]. A study found that 77 % of dermatologic surgeons did not use smoke management precautions in their office [56].…”
Section: Electrosurgerymentioning
confidence: 98%
“…Several are known carcinogens, and others are environmental toxins. 6,7 Smoke management is an important consideration for dermatologists and their patients and generally includes respiratory protection via masks and ventilation techniques. However, the practice is not universal, and oversight agencies such as OSHA and the National Institute for Occupational Safety and Health (NIOSH) provide guidelines only; they do not enforce.…”
Section: Laser Safetymentioning
confidence: 99%
“…Effects of short-term exposure to acrylonitrile and benzene include eye irritation, nausea, vomiting, headache, dizziness, weakness, and light headedness, whereas chronic exposure can result in higher incidence of cancer. [ 1 2 7 8 9 ] Carbon monoxide, hydrogen cyanide, formaldehyde, benzene, and acrolein are also present in plume associated with ablative lasers. [ 10 ]…”
Section: R Isks Of S Urgical S mentioning
confidence: 99%
“…[ 1 ] Surgical plume has been compared to smoking unfiltered cigarettes, with electrosurgical plume being twice as harmful as compared to lasers, hence making its complete evacuation necessary. [ 2 ] Although several guidelines and articles have been published about smoke evacuation in the Western literature, there is paucity of publications in Indian literature. This article aims at discussing methods and proposed strategies to minimize the hazards of surgical smoke.…”
Section: Introductionmentioning
confidence: 99%